Pannexin 1 Channels as an Unexpected New Target of the Anti-Hypertensive Drug Spironolactone. Issue 4 (16th February 2018) - Good, Miranda E.; Chiu, Yu-Hsin; Poon, Ivan K.H.; Medina, Christopher B.; Butcher, Joshua T.; Mendu, Suresh K.; DeLalio, Leon J.; Lohman, Alexander W.; Leitinger, Norbert; Barrett, Eugene; Lorenz, Ulrike M.; Desai, Bimal N.; et al.
Abstract : Rationale: : Resistant hypertension is a major health concern with unknown cause. Spironolactone is an effective antihypertensive drug, especially for patients with resistant hypertension, and is considered by the World Health Organization as an essential medication. Although spironolactone can act at the mineralocorticoid receptor (MR; NR3C2), there is increasing evidence of MR-independent effects of spironolactone. Objective: : Here, we detail the unexpected discovery that Panx1 (pannexin 1) channels could be a relevant in vivo target of spironolactone. Methods and Results: : First, we identified spironolactone as a potent inhibitor of Panx1 in an unbiased small molecule screen, which was confirmed by electrophysiological analysis. Next, spironolactone inhibited α-adrenergic vasoconstriction in arterioles from mice and hypertensive humans, an effect dependent on smooth muscle Panx1, but independent of the MR NR3C2. Last, spironolactone acutely lowered blood pressure, which was dependent on smooth muscle cell expression of Panx1 and independent of NR3C2. This effect, however, was restricted to steroidal MR antagonists as a nonsteroidal MR antagonist failed to reduced blood pressure. Conclusions: : These data suggest new therapeutic modalities for resistant hypertension based on Panx1 inhibition. Abstract : Supplemental Digital Content is available in the text.